Evaluation of Effective Elastic, Piezoelectric, and Dielectric Properties of SU8/ZnO Nanocomposite for Vertically Integrated Nanogenerators Using Finite Element Method. (15th May 2017) - Mishra, Neelam; Krishna, Braj; Singh, Randhir; Das, Kaushik
Abstract : A nanogenerator is a nanodevice which converts ambient mechanical energy into electrical energy. A piezoelectric nanocomposite, composed of vertical arrays of piezoelectric zinc oxide (ZnO) nanowires, encapsulated in a compliant polymeric matrix, is one of most common configurations of a nanogenerator. Knowledge of the effective elastic, piezoelectric, and dielectric material properties of the piezoelectric nanocomposite is critical in the design of a nanogenerator. In this work, the effective material properties of a unidirectional, unimodal, continuous piezoelectric composite, consisting of SU8 photoresist as matrix and vertical array of ZnO nanowires as reinforcement, are systematically evaluated using finite element method (FEM). The FEM simulations were carried out on cubic representative volume elements (RVEs). Four different types of arrangements of ZnO nanowires and three sizes of RVEs have been considered. The volume fraction of ZnO nanowires is varied from 0 to a maximum of 0.7. Homogeneous displacement and electric potential are prescribed as boundary conditions. The material properties are evaluated as functions of reinforcement volume fraction. The values obtained through FEM simulations are compared with the results obtained via the Eshelby-Mori-Tanaka micromechanics. The results demonstrate the significant effects of ZnO arrangement, ZnO volume fraction, and size of RVE on the material properties.